Improved Hypertension Control with the Imidazoline Agonist Moxonidine in a Multinational Metabolic Syndrome Population: Principal Results of the MERSY Study - Irina Chazova; Markus P. Schlaich (International Journal of Hypertension)
This study was designed to assess the effects of moxonidine on blood pressure and aspects of the metabolic syndrome in racially diverse population of patients encountered in routine medical practice. Physicians collected data on a minimum of three consecutive patients with uncontrolled essential hypertension and criteria for metabolic syndrome, eligible to receive moxonidine (0.2–0.4 mg once daily) for 6 months, either as monotherapy or as adjunct therapy to current antihypertensive treatment. Systolic and diastolic blood pressure (BP) declined by an average of 24.5+14.3 mmHg and 12.6+9.1 mmHg, respectively. BP responder rates defined as attaining BP < 140/90 mmHg were significantly (P<0.001) and substantially higher among younger patients, nonpostmenopausal women, and patients receiving monotherapy. While potentially relevant improvements in the entire cohort were observed in regard to body weight (-2.1±5.4 kg), fasting plasma glucose (from 6.8 to 6.2 mmol/L), and triglycerides (2.4 to 2.0 mmol/L), statistically significant changes in metabolic parameters could only be detected in subgroup analyses. Moxonidine therapy reduced blood pressure and improved rates of blood pressure control in this group of patients. While the observed trend towards improvement in various metabolic parameters merits further investigation, the overall effect of moxonidine treatment is consistent with a reduction of total cardiovascular risk in this hypertensive metabolic syndrome cohort.